Penyebab Keterlambatan Jasa Konstruksi Terintegrasi Rancang Bangun Revitalisasi Rusun Penjaringan (Tower A, B, E dan F) Jakarta Utara - Barnet Sitepu; Moh. Azhar; Pio Ranap Tua Naibaho (Universitas Batanghari Jambi, 2026)
Construction project delays are one of the main problems in the construction service industry in Indonesia, which have an impact on increased costs, decreased work quality, and disruption to project completion schedules. The Penjaringan Flats Revitalization Project (Towers A, B, E, and F) in North Jakarta is one example of a project that experienced time constraints due to the complexity of implementation and external factors such as the Covid-19 pandemic. This study aims to identify the factors that influence delays in the Penjaringan Flats Revitalization Design-Build Integrated Construction Services project. The research method used is a qualitative approach with descriptive analysis based on field data, supervision reports, meeting minutes, and project documentation during the 2019–2021 period. The results of the study show that there are nine main variables causing delays, namely situational factors, managerial factors, contract and document scope, planning and scheduling, materials, labor, site characteristics, control, and the Covid-19 pandemic. Of these nine variables, the five dominant factors that significantly influenced delays were cost factors, unexpected events, the experience of supervisors or field managers, and communication between contractors and consultants and between owners and contractors. The conclusion of this study confirms that cost efficiency, external risk management, and good communication and workforce competence are key factors in preventing construction project delays in the future.